IMPLEMENTATION OF PROBLEM-BASED LEARNING ASSISTED BY STRUCTURED STUDENT WORKSHEETS TO IMPROVE JUNIOR HIGH SCHOOL STUDENT’S SCIENTIFIC ARGUMENTATION SKILLS - Veronica Diniarti Mulyana Kusuma Wardani; Waviq Kumala Dwi Alviana; Pramudya Dwi Aristya Putra; Dewi Novi Wardani (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
Scientific argumentation is a critical 21st-century competency that remains underdeveloped among junior secondary school students. This study aimed to improve the scientific argumentation skills of seventh-grade students (Class VII E) at SMP Negeri 11 Jember through the implementation of a Problem Based Learning (PBL) model supported by structured Student Worksheets in the topic of the Solar System. A Classroom Action Research (CAR) design following the Kemmis and McTaggart model was employed, comprising four iterative stages: planning, acting, observing, and reflecting. The study involved 32 participants (17 male and 15 female students) and was conducted over two cycles, each consisting of two instructional sessions. Scientific argumentation ability was assessed using the McNeill and Krajcik (2006) rubric, which evaluates three core components: claim, evidence, and reasoning. Results demonstrated a meaningful improvement in mean argumentation scores, rising from 1.41 (sufficient category) in Cycle I to 1.70 (good category) in Cycle II. In Cycle II, all three components reached the good category, with claim obtaining the highest mean score (1.75), followed by evidence (1.69) and reasoning (1.67). These findings indicate that the integrated use of PBL and CER-based structured worksheets constitutes an effective instructional approach for enhancing scientific argumentation competency among junior secondary school students.